Association between awkward posture and musculoskeletal disorders (MSD) among assembly line workers in an automotive industry - Abdul Rahman, Anita; Amin, Yazdani; Kadir @ Shahar, Hayati; Adon, Mohd Yusoff (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
Automotive industry in Malaysia is one of the booming industries which encompass the design, development and manufacturing of motor vehicles. However, it has its own setback as the interaction between complex tools, machines, and instruments, coupled with humans as workers pose several health hazards. A cross-sectional study was conducted to determine the prevalence of musculoskeletal disorders (MSD) and the association with awkward posture among automotive assembly line workers. A simple random sampling method was adopted and data were collected based on Standardized Nordic Questionnaire (SNQ) and Rapid Upper Limb Assessment (RULA) method for analysing awkward posture. With a response rate of 83%, a total of 232 assembly line workers with at least one year job tenure participated in this study. The findings revealed that 78.4% of workers reported MSD while the highest percentage of complaints concerned the lower back (50.9%). Three factors were found to be significantly associated with MSD: age (χ2=5.61, p=0.018), job tenure (χ2= 8.26, p=0.004) and awkward posture (χ2= 65.37, p < 0.001). Logistic regression analysis indicated that significant risk factors for MSD symptoms were workers aged ≥25 years old (OR= 2.25, 95%CI 1.14-4.46) and those workers with equal and more than three years job tenure (OR= 2.44, 95%CI 1.04-5.63). In addition, workers in the very high and high RULA action level who were 69 times (OR = 69.38, 95%CI 14.51-331.73) and 12 times (OR = 12.42, 95%CI 5.21-29.58), respectively, also had higher odds of complaints of MSD. The high prevalence of MSD shows that MSD symptoms is a significant problem among automotive assembly line workers while age, job tenure and awkward posture based on RULA action level are the significant factors for MSD. In particular, this study proves that the prevalence of MSD increases as the RULA action level and job tenure increases. Thus, this problem could be reduced by decreasing RULA action level through appropriate ergonomic workstation design and ergonomic training for workers.